A Future for the Inland Fish and Fisheries Hidden Within the Sustainable Development Goals - Elliott, Vittoria L.; Lynch, Abigail J.; Phang, Sui C.; Cooke, Steven J.; Cowx, Ian G.; Claussen, Julie E.; Dalton, James; Darwall, William; Harrison, Ian; Murchie, Karen J.; Steel, E. Ashley; Stokes, Gretchen L. (Frontiers in Environmental Science, 2022)
The United Nations Sustainable Development Goals (SDGs) are a unifying mandate for change - guiding global actions at multiple levels of governance. Consequently, achieving the ‘future we want’ may be hindered by overlooking valuable resources that are not explicitly included in the SDGs. Not recognizing their direct, intrinsic value threatens the sustainability of the services they provide and their contributions to the SDGs. Here, we use inland aquatic ecosystems, and their fish and fisheries, as an example to explore options for recognition and inclusion of other overlooked resources. Without highlighting these resources, they are less likely to be incorporated in global, national, and regional objectives, dialogues and policies. We outline multiple potential pathways for better inclusion and capitalization of contributions from overlooked resources during the operationalization of the SDGs and other global instruments.